Rancang Bangun Aplikasi Pengelolaan Nilai Siswa Berbasis Web Pada Rasyid English Course - Hammad, Rifqi; Suhandiah, Sri; Arrosyidi, Achmad (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Rasyid english courses is english  course in the Denpasar city that provide score ofevaluation daily test and the final exam. The score obtained an evaluation recorded by teacher written in score card, then submitted to administration officer using desktopapplication. There are several problems cause losing data when collecting them. First, teachers must come to Rasyid English and then the second one is have to queue to entry data because the entry computer only one so it must be done one by one sequencely. This condition makes the teacher to give the score card to the administration officer. It will takes along time to provide information that will help decision maker for Rasyid english course managers. In the other hand student must come to Rasyid English Course just to know test result eventhought there is nothing else to do. Thus situation both teacher, administration officer and students makes unefficient activity and invalid data to the score management system.Based on the problem above, it will set up an application that can help manager to Rasyid english course to make decision and reduce data loss. Another feature, that can make user entry data anywhere is because use web based application.This research produce web application that guide by SDLC method. This application generate student progress report, academic student report using computer web base application. With web base application allow each the teacher to entry student score anywhere and anytime as long as connected to the internet. Students score can entry by teacher directly without involve the administration officer so the reports can be create as soon as possible.Keywords: Web Applications, Student Progress Reports, Academic Report, English Course